COMPARATIVE DIAGNOSTIC ACCURACY OF DIGITAL AND CONVENTIONAL RADIOGRAPHY IN THE DETECTION OF DENTAL CARIES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Accurate and early detection of dental caries is essential for effective treatment planning and prevention of disease progression. Radiographic examination remains a key diagnostic tool in clinical dentistry; however, the transition from conventional film-based radiography to digital imaging systems has raised questions regarding comparative diagnostic performance. This study evaluates the diagnostic accuracy of digital radiography in comparison with conventional radiographic methods for the detection of dental caries. A comparative clinical study was conducted involving patients undergoing routine dental examination. Both digital and conventional radiographic images were obtained under standardized conditions and independently evaluated for the presence and extent of carious lesions. Diagnostic performance was assessed using sensitivity, specificity, and overall accuracy metrics. The results demonstrated higher sensitivity and improved lesion detectability with digital radiography, particularly for early-stage and approximal caries, while specificity remained comparable between the two methods. These findings indicate that digital radiography offers enhanced diagnostic capabilities without compromising diagnostic reliability. The study supports the clinical use of digital radiographic systems as an effective and efficient tool for the early diagnosis of dental caries.